2013
DOI: 10.1016/j.jtcvs.2013.06.043
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tidal volume on pulmonary complications following minimally invasive esophagectomy: A randomized and controlled study

Abstract: Lung injury due to intraoperative single-lung ventilation may contribute to pulmonary complications after MIE. Low VT ventilation could decrease ventilation-associated lung inflammation, thus minimizing pulmonary complications after MIE. Further studies, based on a larger volume of populations, are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 30 publications
0
50
0
2
Order By: Relevance
“…2). 33,35,[40][41][42][43][44][45][46] Cardiac surgery with cardiopulmonary bypass in and of itself is associated with a systemic and pulmonary inflammation. 47 Cardiopulmonary bypass-related systemic inflammatory response syndrome represents an important first hit for lung injury, and the use of high V T values during the surgery may act as the second hit that worsens lung damage.…”
Section: Ventilation Of Surgical Patientsmentioning
confidence: 99%
“…2). 33,35,[40][41][42][43][44][45][46] Cardiac surgery with cardiopulmonary bypass in and of itself is associated with a systemic and pulmonary inflammation. 47 Cardiopulmonary bypass-related systemic inflammatory response syndrome represents an important first hit for lung injury, and the use of high V T values during the surgery may act as the second hit that worsens lung damage.…”
Section: Ventilation Of Surgical Patientsmentioning
confidence: 99%
“…Other studies demonstrated an association between small intraoperative V T with minimal PEEP and an increased risk of mortality and postoperative complications: low PEEP appears to be insufficient to stabilize alveoli, reduce alveolar strain, and prevent atelectasis (28,29). Application of PEEP is essential to safeguard the lung in surgical patients ventilated with both small and large V T , by improving lung function and reducing the risk of postoperative complications after OLV (13,14,30). In light of the current evidence, it could be suggested that a small V T does not in itself prevent postoperative respiratory complications without adequate PEEP, and it is interesting to note that in the most important studies, the duration of OLV was longer than that used in the present study ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The duration of OLV seems to be one of the major factors influencing a patients' outcome, aside from the quality of postoperative analgesia and intraoperative fluid therapy, in positive correlation with the length of an ICU stay (34). If put into practice, approaches and techniques that would achieve the optimization of these factors could improve patient outcome and reduce critical care resources required for patients undergoing thoracic surgery (30).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the pathophysiologic relevance of capnothorax was also investigated by Mao et al [25] who found relevant impairment of the coagulatory system in patients after capnothorax. Also, experimental work by Shen et al [26 ]demonstrated that changes in pulmonary management with low-volume insufflation significantly reduced postoperative pulmonary complications in patients undergoing esophagectomy with cervical anastomosis. Robotic-assisted minimally invasive esophagectomy (RAMIE) is technically equivalent to total MIE and mainly performed in the setting of single-lung ventilation; however, the steady image and the exact movement of the instruments may further reduce the physiologic alterations during the operation.…”
Section: Types Of Minimally Invasive Esophageal Resectionmentioning
confidence: 99%